Linking entrepreneurial orientation to firm performance in a post-socialist market context : the case of Hungary - David Kovacs; Katrin Zulauf; Taylan Ürkmez; Dominik Brockhaus; Ralf Wagner (Management dynamics in the knowledge economy, 2016)
Entrepreneurial orientation provoked the interest of numerous scholars as well as political and administrative decision-makers. Both start-ups and already established corporate entities are increasingly persecuting new opportunities, products, and business models in order to establish superiority above their competitive environment. The tendencies evince an optimist impact of entrepreneurial orientation on business performance, namely on financial performance. Beyond the aforementioned relationship, there are impulses such as environmental and organizational factors, which are affecting the businesses. The results of this study provide evidence of the effect of entrepreneurial orientation on business performance in a post-socialist context. We test the impact of three moderators on this bivariate relationship. In contrast to the substantial body of literature for Western markets, we contribute to minimizing the considerable gap of research in post-socialist economies. Entrepreneurial orientation as an organizational behavior may affect the financial performance of businesses differently in distinct market contexts. Both, internal and external factors are crucial to identifying, analyze and monitor, to achieve superior performance and to overcome competitors. This study builds upon a stratified sampling survey of Hungarian company owners and managers from the Amadeus database. The study uses a deductive approach. For the analysis, we rely on structural equation modeling using the PLS algorithm. Our study contributes to the existing literature by means of confirming the entrepreneurial orientation to firm performance relationship for Hungary. In this context, we test the moderating effects of environmental dynamism, environmental hostility as environmental factors and firm age as an organizational factor. Environmental hostility is closely related to an unfavorable environment, deriving from rapid and radical changes in the industry, which are typical for post-soviet economies. In such dynamic environment, destructive innovations of the industrial actors appear more often as the economy switches to an open competition, capitalist market. The results confirm that the internal and external factors have no significant influence on the entrepreneurial orientation to financial performance direct relationship.
2819566-8; 2392-8042; Management dynamics in the knowledge economy; 823675920